Benefício das gliflozinas na abordagem do paciente com insuficiência cardíaca de fração de ejeção reduzida - Oliveira, Luan Cayke Marinho de (2021)
Heart Failure (HF), according to the guidelines of the American Heart Association (AHA), is a complex syndrome composed of a set of signs and symptoms resulting from structural and/or functional impairment of the heart, which is considered a public health problem with high hospital costs, generating a high associated morbidity and mortality when not managed early and effectively. New drugs have emerged with proven efficacy in the treatment of patients with Heart Failure with Reduced Ejection Fraction (HfrEF), among them, the class of sodium glucose linked transporter (SGLT2) inhibitors have gained notoriety, because they significantly reduced hard outcomes (death and hospitalizations) in patients with HF when added to the standard triple treatment. The present study aims to identify and describe the benefits of SGLT2 inhibitors (gliflozins) in the therapy of HFFEr patients. A basic, descriptive, literature review of 19 articles aimed at expanding knowledge was performed. Articles were included from the last 03 years (2019 - 2021), in the English language that contained the descriptors "Heart Failure"; "SGLT2 inhibitors"; "Reduced Ejection Fraction" and " Patient Outcomes", applied in the National Library of Medicine (PubMed) databases. Most articles showed that Empagliflozin, Dapagliflozin and Canagliflozin are drugs that reduce cardiovascular mortality, hospitalization for HF and improve quality of life in both type 2 diabetic and non-diabetic patients. Regarding safety of the drugs, Canagliflozin was shown to be more associated with adverse effects such as bone fracture and amputation of the foot and midfoot. In this review, it is concluded that iSLGT2 drugs are safe and effective in reducing morbidity and mortality and decreasing the progression of renal dysfunction in patients with ICFEr. In addition, further trials are needed to study the mechanisms by which iSGLT-2 promotes beneficial effects in order to increase the understanding of this class of drugs that hold promise for better outcomes in this group of patients.